Two plants improve stress response of a subterranean herbivore by downregulating amphetamine addiction pathways - Zhang, Feiyu; Tan, Yuchen; Cai, Zhiyuan; An, Kang; Liu, Yongjie; Su, Junhu (Frontiers in Veterinary Science, 2024)
Captivity serves as the primary method for enhancing animal survival and productivity. However, the stress induced by confinement can hinder animal growth and reproduction. The administration of drugs to captive animals can effectively regulate their stress response and can also be used inartificial breeding, reproduction, and experimental animalization of wild species. The plateau zokor (Eospalax baileyi), a subterranean herbivore, experiences significant stress during the captive process owing to its unique habitat. In our study, we utilized Radix astragali (RA) and Acanthopanax senticosus (AS) extracts to intervene in the stress response of plateau zokors. Our findings demonstrated that RA and AS treatment considerably improved food intake and reduced weight loss, stress-related behavior, and stress hormone levels in plateau zokors. Furthermore, the excitatory pathway of amphetamine addition in the hypothalamus was suppressed by RA and AS treatment, acting through the Grin and Prkc gene families. Notably, after RA treatment, the extracellular matrix-receptor interaction pathway, enriched by the Col1a1/3a1/1a2/6a1 gene, was significantly upregulated, potentially enhancing the immune function of captive plateau zokors. In conclusion, our research demonstrates that RA and AS treatment can effectively alleviate the stress response of plateau zokors in captive environments. The downregulation of the excitation pathway and upregulation of the immune pathway offer valuable insights into the response and potential mechanisms of plant-based drugs in mitigating animal stress.